Who Is Doing the Chores and Childcare in Dual-Earner Couples during the COVID-19 Era of Working from Home? - Sabrina Wulff Pabilonia; Victoria Vernon (Institute of Labor Economics (IZA), 2022)
In 2020, parents' work-from-home days increased fourfold following the initial COVID-19 pandemic lockdown period compared to 2015–2019. At the same time, many daycares closed, and the majority of public schools offered virtual or hybrid classrooms, increasing the demand for household-provided childcare. Using time diaries from American Time Use Survey (ATUS) and looking at parents in dual-earner couples, we examine parents' weekday workday time allocated to paid work, chores, and childcare in the COVID-19 era by the couple's joint work location arrangements. We determine the work location of the ATUS respondent directly from their diary and proxy the partner's work-from-home status using the share of workers reporting work from home in their occupation. When their partners worked on-site, mothers and fathers working from home spent more time on childcare, especially mothers, compared to those on-site; fathers spent more time on household chores. However, only mothers' total unpaid and paid work burden was higher. In the fall, fathers working from home worked substantially fewer paid hours and spent even more time on household production. When both parents worked from home compared to both worked on-site, mothers and fathers working from home worked roughly equally fewer paid hours and did more secondary childcare, though fathers did more household production, suggesting they shared the increased work burden resulting from the pandemic more equally. However, in the fall, only mothers did more childcare when both worked from home. We also find that mothers spread their work throughout the day when working from home.
Keywords: D13; J22; J29; 330; COVID-19; household production; childcare; telework; remote work; working from home; gender care gap; gender inequality; pandemic parenting